Immunologics and Chemotherapeutics for Renal Cell Carcinoma - Diamond, Elan; Riches, Jamie; Faltas, Bishoy; Tagawa, Scott T.; Nanus, David M. (Seminars in Interventional Radiology, 2014)
Treatment of metastatic renal cell carcinoma remains a challenge for clinicians. Traditional chemotherapy is ineffective and immunotherapy with interleukin-2 is only occasionally beneficial. The development of numerous agents targeting vascular endothelial growth factor and mammalian target of rapamycin signaling pathways that have been studied in phase III trials have resulted in significant improvement in survival for patients with clear cell renal cell carcinoma. Currently available U.S. Food and Drug Administration-approved first line targeted agents include sunitinib, pazopanib, temsirolimus, and bevacizumab (with interferon), while axitinib, everolimus, and sorafenib are most extensively used following progression as second- or third line therapy. Attempts to augment the activity of these agents by combining them together or with chemotherapy or immunotherapy have not yet proven to improve outcomes. As a result, the sequential use of single agents remains the current standard of care.
Keywords: chemotherapy; renal cell carcinoma; VGEF inhibitors; mTOR inhibitors; interleukin-2; interventional radiology